Valuation of the use of Podcasting for clinical education in the area of restorative dentistry - Saravia, Miguel (2020)
Objective: To describe the valuation of podcasting as a tool in the learning process by dental students at a private university. Material and methods: The research was quantitative, descriptive, and non-experimental.  The sample consisted of 47 students from a dental school. For the experience, articles in PDF format from the theoretical classes were recorded using conventional headphones and the application Spreaker REC®, a free application that was installed in a smartphone Iphone 8. The article in PDF format was processed, recorded and edited in less than 15 minutes using said application. Subsequently, the link was sent to the WhatsApp® group so the students could access the audio. The podcast could be repeated as many times as the student desired. Three podcasts were made. The information was collected through surveys using a Licker-type survey. Results: The 70.22% of the respondents considered that the shared podcasts in the WhatsApp® group had a high and very high contribution to their clinical performance. It was found that the podcasts were of easy consultation (95,74%), facilitated learning (75,74%) and contributed to a shorter learning time (93,62%). Overall, 62,07% considered podcasting a good resource for the theoretical content. Conclusions: Students consider that podcasting is a tool that contributes to their learning, particularly as a very useful vehicle for learning theoretical content.